"دور مكاتب العبور في تسهيل التجارة الخارجية في الجزائر - دراسة حالة مكتب عبور شركة تريمكس- " - حمزة, هزلة; البشير, مصباحي; حسام, ركابي (جامعة الوادي - University of Eloued, 2023)
" ان تطور الحاصل في التجارة الخارجية وزيادة حجم المبادلات التجارية جعلت المتعاملون الاقتصاديون يعتمدون في اغلب الأحيان على وسيط يسمى وكيل العبور، والذي يقوم بتنفيذ إجراءات الإدارية وتنظيمية. يعمل وكيل العبور تحت حساب موكله على إعادة البضاعة بعد استلامها، اما في الجزائر فينحصر عمله على القيام بالإجراءات الجمركية فقط، وذلك لعدم وجود قانون خاص به، غير انه يجود هيئات دولية وأخرى داخلية تكفلت بمهمة تنظيم وتطوير نشاطها ودورة في تسهيل التجارة الخارجية. ويهدف هذا البحث لمحاولة فهم مكانة ودور وكيل العبور، في تسيير التجارة الخارجية ومعرفة العملية تخليص البضاعة (داخل وكالة العبور)، ولذلك لأجراء دراسات منهجية وثائقية، حيث سيتم اتخاذ شركة تريمكس (TRIMAX) كمرجع تطبيقي للدراسة. " " The foreign trade's development and the increase in the volume of commercial exchanges Made economic operators depend in most cases on a mediator called the transit agent, who Carries out administrative and regulatory procedures. In general, the transit agent works for his client to return the goods after receiving them, While in Algeria, his work is limited to carrying out customs procedures only because there is No special law for him, but there are international unites and internal bodies that have the Task of organizing and developing his activity and his role in facilitating foreign trade. This research aims to try to understand the status and role of the transit agent in the Conduct of foreign trade and know what the process of clearing the goods in order is To conduct systematic and documentary studies and take the TRIMAX Company as an applied Reference for the study."
Keywords: تسهيل التجارة الخارجية، وكيل العبور، الإجراءات الجمركية، البضائع.; Transit agent, customs procedures, and goods.